A COMPARATIVE ANALYSIS OF BODY PART PHRASEOLOGICAL UNITS IN ENGLISH AND KARAKALPAK LANGUAGES - Toreniyazova Diloram,; D.T.Xadjieva, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: Phraseology is a branch of linguistics that studies stable combinations, phraseologisms, and set expressions, revealing the relationship between language and culture. These expressions are considered the “cream” or “core” of language because of their rich semantic content. In particular, phraseologisms related to body parts reflect people’s emotions, life experiences, and social relations. In recent years, the use of body parts in expressions has prompted numerous studies. This article examines linguistic tools related to body parts in Karakalpak and English languages, focusing on their cultural significance, usage in everyday life, and origins.